Untouched minds in a tangled web: navigating mental autonomy and epistemic welfare amidst digital propaganda - Yildirim-Vranckaert, Emine Ozge; Hyzen, Aaron (Frontiers in Communication, 2025)
In this article, we propose a new theoretical account of mental autonomy through which policymakers can develop new legal instruments to mitigate the harms caused by propaganda. We argue for a renewed understanding of mental autonomy, informed by relational autonomy, highlighting its interdependent nature, shaped by technological mediation and social structures in the digital public sphere. We begin by defining propaganda and discussing its potential to inflict harm through the transformational forces of datafication, algorithmization, and plaformization. A historical review of legal approaches to propaganda reveals critical gaps in existing frameworks, which continue to rely on outdated perceptions of autonomy that assume the mind is largely immune to external influences. To address these inadequacies, we build upon the novel concept of epistemic welfare—societal structures and conditions to ensure epistemic agency—and extend it to mental autonomy, which we argue is a necessary precursor to such welfare. Finally, while recognizing the challenges of implementing legal protections against propaganda, we advocate for a governance approach that balances protection and freedom within the broader notions of free thought and expression.